Water perspectives in emerging countries : integrating ecosystems in coastal engineering practice (INECEP) : proceedings of the Summer School September 18-30, 2017 - Puerto Morelos, Mexico - Silva, Rodolfo; Chávez, Valeria; Bahadir, Müfit (Cuvillier Verlag, 2017)
Coastlines around the world are facing significant damage from increasing urban development and population density, additional infrastructure of diverse sectors and ecosystem degradation. Engineers are increasingly called upon to provide structures that give protection against wave attack, coastal flooding and erosion. Generally, these protective measures are hard barriers, which are designed with little or no consideration of their impact on ecosystems or possible adaptation to climate and global changes. However, natural solutions have begun to emerge, which replace or are incorporated into conventional protection schemes. Even so, the more conventional structures are those frequently adopted, as there is a lack of knowledge, methodical frameworks, models, analysis tools, and practical guidance for the implementation of more ecologically based schemes. The Summer School in Puerto Morelos, Mexico, on Integrating Ecosystems in Coastal Engineering Practice (INECEP) held in September 18-30, 2017, organized by Exceed Swindon - Latin America Network was conceived to bridge this gap. As a response to recent natural disasters, such as flooding and erosion in coastal areas, research and development in ecosystem-based approaches have advanced greatly. Knowledge on the interactions between protection structures and coastal ecosystems, evaluation, modelling and mapping of coastal ecosystem services, methodological frameworks and tools for eco-engineering was provided to the attendees, enabling them to move from conventional coastal protection to nature-based and hybrid coastal protection solutions. The papers in this book are some of the case studies examined during this course.